Here's the question you clicked on:
Raeee_009
-(2x-6) expand brackets
Using Distributive property you can do it.. Multiplication by minus sign here means multiplication by -1./.. so according to distributive property a*(x+y)=a*x+a*y also -1*-1 = 1 -1 * 1 = -1 1*1 = 1 ie -ve multiplied by -ve = +ve +ve multiplied by -ve = -ve -ve multiplied by +ve = -ve +ve multiplied by +ve = +ve hope now you can do it now by yourself
Here * means Multiplication
that is a*b = c means a is multiplied by b and the answer is c
on multiplying -ve with -ve, u get +ve. -ve*+ve gives _ve.
@Raeee_009 are you following?
dont understand any of that
ok..Let us start from the beginning... expand bracket means multiplying the terms outside the bracket with the terms inside.. that is for example 1.expand bracket a*(x+y) means multiply 'a' with the terms inside the bracket You understand that??
well good.. so what are the terms inside the bracket in a*(x+y) ?
@Raeee_009 is it .. axy?? Here if we want to find the term inside bracket of blow question s*(t) inside the bracket term means the term inside the symbols ( ) here the term is side the symbol is 't' the term outside the bracket means the term outside the symbol ( ) here the term outside that symbol is s... understood?
so if that is the case can you tell me so what is the term inside the bracket in a*(y) ?
let me try with a diagram : |dw:1354020400786:dw|
@Raeee_009 You get what I am trying to say?
kind of /: but not fully can you do an example with actual numbers
ok... 2*(5+3) this means we have to multiply the term outside the bracket (here 2) with terms inside the bracket (5+3) what this means is that we have to multiply 5 by 2 and 3 by 2 and have to add the result that is 2*(5+3) = 2*5 +2*3 = 10 + 6 = 16 you got this
By looking the diagram that @hartnn posted may facilitate your learning
yeah i understand that
well.. good can you solve this then? expand bracket 2*(2+6)
2*2=4 and 2*6=12 so 4+12